A cross sectional study of contraceptive use and reasons for unmet needs among mothers attending immunisation clinic at tertiary care centre of central India - Dethe, Archana; Kaswan, Pradeep; Shidam, Umakant G.; Gawande, Bhagyashree S.; Kaur, Daljeet (International Journal Of Community Medicine And Public Health, 2020)
Background: Unmet need of contraception remains a national problem. The study was conducted among the mothers attending immuno-prophylaxis clinic (IPC) at tertiary care centre of central India to determine the use of different types of contraception and assess the unmet need for contraception along with the reasons associated with the unmet needs of contraception. Aim and objective was to study the contraceptive use, reasons for unmet needs amongst the mothers attending IPC and some related factors. Methods: This was a cross-sectional study conducted during the period from February-April 2016 at IPC in tertiary care setting. In this study 280 mothers attending IPC for Measles and DPT 1st booster of their child were enrolled. The sample population was selected by simple random sampling method. A pre-tested structured questionnaire was used to collect data from the respondents with written informed consent. Results: This study shows that, 65% of mother told they were practicing any type of family planning method. Unmet need for contraception was 37.14 per cent. Among those having unmet need (n=104), fear of side effects (41.35%), infrequent sex (25%) were the common reasons for unmet need. Religion, age of marriage, age at 1st pregnancy, education, socioeconomic status, occupation of husband, counselling about contraceptives during ANC/PNC visits and resumption of menses were significantly associated with the use of contraceptives. Conclusions: The unmet need for contraception was quite high. Most of the study subjects were not using contraception due to fear of side effects and lack of knowledge.